Platelet-rich fibrin-a cost-effective, donor less and indigenous therapy for obtaining root coverage-a case report - Joshi, Bharat (International Journal of Dental Research, 2017)
Among the periodontal infections, gingival recession is a separate clinical entity which demands a permanent solution plan. Treatment therapies are based on either elimination (as in case of Millerâ€™s class I/II recession) or increasing the width of keratinized gingiva for prevention of further progression (as in case of Millerâ€™s class III/IV recession). From the centuries, graft surgeries like free gingival graft, lateral pedicle and Coronally advanced flaps have been successful in the Â treatment of gingival recession. As every technique has its own merits and demerits, clinicians have tried to stress upon addition of certain adjuncts or biomaterials to ensure rapid healing and less post-operative discomfort. Platelet concentrates are an excellent biomaterials for increasing width of attached gingiva and enhancing wound healing. They are cost effective, do not require donor tissue for harvesting and contain variety of growth factors for initiating regeneration. In this paper, Platelet-rich fibrin a 2nd generation concentrates has been used as an adjunct to Coronally advanced flap with a purpose of increasing width of keratinized gingiva, obtaining complete root coverage and achieving gingival harmony.